Silencing Long Non-coding RNA LINC01224 Inhibits Hepatocellular Carcinoma Progression via MicroRNA-330-5p-Induced Inhibition of CHEK1 - Gong, Dan; Feng, Peng-Cheng; Ke, Xing-Fei; Kuang, Hui-Lan; Pan, Li-Li; Ye, Qiang; Wu, Jian-Bing (Molecular therapy. Nucleic acids, 2020)
Hepatocellular carcinoma (HCC) accounts for approximately 85%-90% of primary liver cancers. Based on in silico analysis, differentially expressed long non-coding RNA (lncRNA) LINC01224 in HCC, the downstream microRNA (miRNA) miR-330-5p, and its target gene checkpoint kinase 1 (CHEK1) were selected as research subjects. Herein, this study was designed to evaluate their interaction effects on the malignant phenotypes of HCC cells. LINC01224 and CHEK1 were upregulated and miR-330-5p was downregulated in HCC cells. miR-330-5p shared negative correlations with LINC01224 and CHEK1, and LINC01224 shared a positive correlation with CHEK1. Notably, LINC01224 could specifically bind to miR-330-5p, and CHEK1 was identified as a target gene of miR-330-5p. When LINC01224 was silenced or miR-330-5p was elevated, the sphere and colony formation abilities and proliferative, migrative, and invasive potentials of HCC cells were diminished, while cell cycle arrest and apoptosis were enhanced. Moreover, LINC01224 induced HCC progression in vitro and accelerated tumor formation in nude mice by increasing CHEK1 expression. The key findings of the present study demonstrated that silencing LINC01224 could downregulate the expression of CHEK1 by competitively binding to miR-330-5p, thus inhibiting HCC progression. This result highlights the LINC01224/miR-330-5p/CHEK1 axis as a novel molecular mechanism involved in the pathology of HCC.